Restoring your spiritual passion - MacDonald, Gordon (Guilford, UK Highland, 1989)
Includes bibliographical references.
Copy 2 donated by Pieter Dijkstal, 5/2003. See also "Restoring Joy" by Gordon MacDonald.
Keywords: Christian life